Microencapsulation of extracted Garcinia Mangostana (GM) pericarp: article - Anak Jerry, Timothy Alvin; Ibrahim, Ummi Khalthum (2017)
Garcinia Mangostana (GM) fruit is one of the most popular fruit and known as a tropical fruit that has high nutrition value and widely cultivated in the tropical rainforest of some Southeast Asian nations. The abundance of mangosteen pericarps during fruit season have been collected and reviewed the contents of pericarp in order to investigate the beneficial antioxidants of mangosteen percarp fruit by using different methods. The main objectives for this research are to identify the composition of extracted xanthones in encapsulated Garcinia Mangostana (GM) pericarp and to determine the antioxidants activity, total phenolic content, moisture content and antimicrobial activity of encapsulated Garcinia Mangostana (GM) pericarp. The scope of research focuses on discovering and identifying the properties of xanthones from Garcinia Mangostana (GM) pericarp which can produce microencapsule. The main method that involves in this research is solvent extraction by using soxhlet extraction and microencapsulation by using freeze drying. DPPH antioxidant activity, total phenolic content (TPC), moisture content and antimicrobial activity are the basic analysis that have been done to determine the properties of extracted xanthones from Garcinia Mangostana (GM) pericarp. The amount of extracted xanthones in form of liquid from 20 gram of Garcinia Mangostana (GM) pericarp is only 22 ml whereas all samples have been detected in the range of 515.0 to 4000 cm-1 through Fourier transforms infrared spectroscopy (FTIR). The highest value of radical scavenging activity before the samples has been freeze dried is 82.69% whereas 88.01% for samples of powder. Furthermore, the total phenolic content (TPC) of xanthone is 5.240 mg GAE/g before freeze drying and 6.359 mg GAE/g after freeze drying. The highest moisture content for the powder of extracted xanthone from Garcinia Mangostana (GM) is achieved 7.02 %M. For the antimicrobial activity, most of samples only have single colony of microbes on agar plate after 72 hours incubated in 37 ⁰C. In conclusion, extracted xanthones from Garcinia Mangostana (GM) pericarp has higher content of antioxidant which functions as inhibitor to the free radical activities and benefit to the manufacturing food, cosmetic and also pharmaceutical.